A new species of Specklinia (Orchidaceae, Pleurothallidinae) from Colombia - Kolanowska, Marta (Biodiversity: Research and Conservation, 2012)
During field work conducted in Colombia, a new species of the genus Specklinia Lindl., S. pereziana was found. The new species is described and illustrated. Information about its habitat and ecology is provided. Specklinia pereziana is similar to S. muricaudata, from which it differs in leaf shape and floral characters - the main differences between the species are discussed.